Study On The Development Of Ceramic Cutting Tool (ZTA / ZTA-MGO) And Its Machining Performance In Slot Milling - Hassan, Mohd Nor Hakim (2010)
From the various cutting insert materials available, ceramic materials have the potential to be used as cutting insert due to the attractive properties such as high hot hardness, abrasion resistance and chemical stability but the base material suffers from the limitation of low fracture toughness and low thermal shock resistance capability. Yttria stabilized zirconia (YSZ) and magnesia (MgO) were introduced into the alumina (ceramic material) in order to toughen the brittle ceramics. Previous studies found that an addition of 0.7 wt % of MgO into the Zirconia Toughened Alumina (ZTA) matrix (80 wt % alumina + 20 wt % YSZ) as an insert in lathe machining, produced minimum wear area. However, the potential of these cutting insert compositions were not carefully investigated in lathe or milling operation. Therefore, this research investigated the potential of these inserts from ZTA material, ZTA reinforced with MgO and commercial available cutting insert in slot milling operation and three objectives were indentified. Firstly, to design and fabricate die used for pressing ceramic powder. Secondly, to investigate the performance of these inserts and thirdly, to compare the performance of these inserts with chosen Kennametal ceramic insert at the same slot milling operation. The die was designed using Catia V5R17 software and fabricated using SKD 11 tool steel. Raw materials consist of alumina, YSZ and magnesia were mixed with desired composition for eight continuous hours in mixing bottle. Hydraulic pressed were carry out using fabricated die to obtain the green body insert.